Justiça distributiva: uma leitura da obra de John Rawls - Trindade, Ubiratan (Universidade do Vale do Rio do Sinos, 2008)
A fairer income distribution has been debated as a way of making viable the democratic societies with liberal characteristics. The problem to be examined in this investigation is exatly the possibilities that the governments called liberal have, promoting reforms that result in such possibilities. In this way, we will be giving focus on the work A theory of justice from the American philosopher Jhon Rawls. Inserted in the contractualist traditions, it elaborates a justice as fairness, placing itself as an alternative to the utilitarian doctrine. The democratic governments, according to Rawls, must ensure that public politics have a consistent distributive justice as a consequence. These governments must be plural, and conflits of philosophical, moral or religious order must not prevent a reasonable agreement as a way of making viable a basic structure of the society. Using a rational artifice in which the agreementes are valid for everyone, Rawls creates the artifice of original position. In this situation th
Keywords: democracia; justiça distributiva; liberalismo; posição original; princípios de justiça; sociedade; John Rawls; distributive justice; liberalism; original position; principles of justice; society; democracy; Ciências Humanas